Clinical indicators for the initiation of endotracheal suction in children: An integrative review - Davies, K.; Monterosso, L.; Bulsara, M.; Ramelet, Anne-Sylvie (Elsevier Ireland Ltd, 2015)
Background: Critical decisions and interpretation of observations by the nurse caring for the paediatric intensive care (PIC) patient can have dramatic and potential adverse impact on the clinical stability of the patient. A common PIC procedure is endotracheal tube (ETT) suction, however there is inconsistent evidence regarding the clinical indicators to guide and support nursing action. Justification for performing this procedure is not clearly defined within the literature. Further, a review of the literature has failed to establish clear standards for determining if the procedure is warranted, especially for paediatric patients. Objective: The objective of the review is to identify current clinical indicators used in practice to determine why ETT suction should be performed. Method: An integrative review using a systematic approach to summarise the empirical and theoretical evidence within the literature as it relates to clinical practice was used. Results: Consensus of opinion indicates that ETT suctioning should only be performed when clinically indicated. There is no general consensus regarding which clinical indicators should be measured and used to guide the decision to perform ETT suctioning. Conclusion: Research is required to identify the clinical indicators that could be used to design a valid and clinically appropriate tool to use to assist in the decision making process to perform ETT suction.